Psychological functioning in children with low birth weight - Haycock, Anna Cornelia (University of Limpopo, 2008)
Low-birth-weight/premature children seem to be vulnerable to psychiatric, neuropsychological and other deficiencies. Limited research is available in the South African context about these ever-increasing phenomena. The aim of this study was to investigate the magnitude and characteristics of internalising (Separation Anxiety, Overanxious and Major Depressive Disorders) and externalising symptoms (Attention-Deficit/Hyperactivity, Oppositional Defiant and Conduct Disorders) among low-birth-weight children in comparison with normal-birth-weight children, as well as to establish neuropsychological deficiencies (motor, visual-spatial, memory and executive functioning) between the birth weight groups, analysed as a function of gender and age. The sample (158 children) was selected from nine urban mainstream primary schools in the Tshwane North and South districts by means of stratified random sampling. Low-birth-weight children (weighing below 2 000 g) (N=79) were matched with normal-birth-weight children (above 3 000 g) (N=79) according to age, gender, language and socio-economic status. The neuropsychological test battery and self-reporting questionnaire were individually administered to the sample at the selected schools during school hours. Teachers and parents of selected participants were requested to complete a rating scale. As expected, low birth weight is associated with a tendency towards increased internalising and externalising psychological symptoms, as well as poorer neuropsychological functioning. This was particularly significant in the domains of internalising symptoms (depression), externalising symptoms (hyperactivity/impulsiveness, inattention, Oppositional Defiant Disorder and Conduct Disorder) and neuropsychological impairments (motor, visual-spatial/visual-motor, memory and executive functioning). The neuropsychological impairments observed in this study among the LBW children probably increase the risk of subsequent externalising (conduct and oppositional behavioural problems) and internalising (depressive) psychological symptoms. These impairments are possibly exacerbated by inattention and hyperactivity/ impulsiveness. Reciprocal interaction seems to take place between the psychological symptoms andneuropsychological functions. Only a few gender differences were observed. Neuropsychological deficits were observed both in the 6 to 9 and 10 to 13 age groups, indicating deficient resolution of impairments with increasing age. Increased pre-, peri- and postnatal complications in the low-birth-weight group may predispose these children biologically to neuropsychological deficiencies and subsequent internalising/externalising symptoms. These impairments most probably affect academic, emotional, social and other significant areas of functioning, increasing public health cost.
Thesis (PhD. (Clinical Psychology)) --University of Limpopo, 2008
Keywords: Low birth weight; Premature children; Birth weight, low; Premature infants